2019
DOI: 10.1643/ch-19-213
|View full text |Cite
|
Sign up to set email alerts
|

A Lentic Breeder in Lotic Waters: Sierra Nevada Yellow-Legged Frog (Rana sierrae) Habitat Suitability in Northern Sierra Nevada Streams

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…At Lone Rock Creek, tadpoles and subadults were found more often adjacent to the deep runs and pools behind beaver dams, whereas adults were found more often in the riffles upstream. Similar to Yarnell et al (2019, in this volume), we generally found frogs in shallow water, and those authors suggested frogs find similar microhabitats within what may appear to be diverse habitats at larger scales. However, we caution against using simple habitat suitability cutoffs to make specific management decisions given the extensive breadth of habitats used by the species as seen here.…”
Section: Discussionsupporting
confidence: 89%
“…At Lone Rock Creek, tadpoles and subadults were found more often adjacent to the deep runs and pools behind beaver dams, whereas adults were found more often in the riffles upstream. Similar to Yarnell et al (2019, in this volume), we generally found frogs in shallow water, and those authors suggested frogs find similar microhabitats within what may appear to be diverse habitats at larger scales. However, we caution against using simple habitat suitability cutoffs to make specific management decisions given the extensive breadth of habitats used by the species as seen here.…”
Section: Discussionsupporting
confidence: 89%
“…This may explain the shift to off-channel habitats at Independence and use of floodplain pools by subadults at Lone Rock during high flows. This generally agrees with Yarnell et al (2019) who found that frogs preferred shallow and low velocity water, which they find in a variety of geomorphic unit types. Our analyses add nuance to this result, however, by using a random slope model that explicitly accounted for habitats available at the time of survey (seasonal units), flows (hydrologic index), and streams, and by explicitly modeling the interaction between depths and flow (presence and water velocity).…”
Section: Perennial Channelssupporting
confidence: 91%
“…We studied six occupied reaches of four streams in R. sierrae's northern range that varied by size, hydrology, geomorphology, and frog abundance (Fig. 1; Yarnell et al 2019). Perennial Lone Rock Creek (2.7 km) and Independence Creek (0.66 m) are low-to-moderate gradient, second-and third-order reaches (Fig.…”
Section: Study Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our data suggest this is unlikely to be a major concern for current conservation management, at least currently (see below). While there is a potential for misclas- (Bondi, Yarnell, & Lind, 2013;Yarnell et al, 2019), but Rana sierrae are uniquely adapted to persist in short-growing periods common in the high Sierras (Bradford, 1983;Knapp et al, 2003). Rana sierrae tadpoles may overwinter multiple years before metamorphosing, thus R. sierrae may have diverged from R. boylii because of their ability to persist in colder climates, common during periods of glaciation during the Pleistocene.…”
Section: Discussionmentioning
confidence: 99%